Polyacrylic Acid With Amide Crosslinks Decorated With Silver Nanoparticles: Synthesis And Application In Waste Water Treatment - Abu Hafeth, Naba (جامعة النجاح الوطنية, 2019)
In this study, Polyacrylic Acid with amide crosslinked (PAA) was decorated with Silver Nanoparticles (NPs). The resulting polymers PAA and PAA with silver NPs (PAA-Ag) were characterized by IR spectrophotometer. Both were used as adsorbents for Lead(II) and 5- Fluorouracil from aqueous solutions. The adsorption efficiency of each adsorption process was investigated as a function of adsorbent dose, adsorbate concentration, contact time, temperature and pH value. Tendency of prepared PAA-Ag for extracting Pb(II) from water was evaluated and compared to PAA. It was observed that adsorption of lead on PAA-Ag and PAA was affected by the amount of PAA-Ag until the equilibrium level. The optimum pH value for lead adsorption was 7.33 and 4.7 for PAA-Ag and PAA respectively and the equilibrium was established within the first 10 min adsorption was done at room temperature. It was found that Lead adsorption kinetics has followed pseudo-second-order. Experimental data were analyzed using two model equations: Langmuir and Freudlinch and it was found that the data fitted well with Freundlich isotherm model. Meanwhile, PAA-Ag was used as adsorbents for the removal of 5-FU from aqueous solution. The concentration of 5-FU in the supernatant was measured by UV-vis spectrophotometer. It was observed that adsorption of 5-FU was affected by the amount of PAA-Ag until the equilibrium level. The optimum pH value for 5-FU adsorption was 8.18 and the equilibrium was established in 5 min. It was also evident that the adsorbed 5-FU was decreasing as the concentration of 5- FU was increased in solution. It was found that 5-FU adsorption kinetics has followed pseudo-second-order. And it was found that the data fitted well with Langmuir isotherm model
مُبلمر حمض الأكريلك المُعدل بالأميد ودقائق الفضة النانوية: تحضيره وتطبيقاته لمعالجة المياه العادمة